Histologic evaluation of pulpotomy performed with ethyl-cyanoacrylate and calcium hydroxide Avaliação histológica de pulpotomia realizada com etil-cianoacrilato e com hidróxido de cálcio - Diana Santana de Albuquerque; Luciana Ferraz Gominho; Roberto Alves dos Santos (Sociedade Brasileira de Pesquisa Odontológica, 2006)
The aim of this study was to evaluate histological aspects of the pulp-dentin complex of dogs submitted to pulpotomy and capped with ethyl-cyanoacrylate and calcium hydroxide. Thirty dog teeth were divided into 2 groups of 15 as follows: Group 1 - ethyl-cyanoacrylate; Group 2 - calcium hydroxide. The pulpotomies were carried out following all of the treatment precautions recommended for dogs. After 30 days the specimens were submitted to histological preparation and were then blindly evaluated by a histologist. Data were analyzed statistically by the Fisher exact test, comparing the two groups. After 30 days, the presence of a hard tissue barrier was observed in 83.3% of Group 1, and in 100% of Group 2 (p = 0.478). A continuous hard tissue barrier was observed in 50% of the ethyl-cyanoacrylate group and 75% of the calcium hydroxide group (p = 0.652). It can be concluded that both materials induced hard tissue barrier formation, but Group 2 had a higher percentage than Group 1, with no significant statistical differences; the differences observed between the different barriers (continuous/non-continuous) were not significant between groups and there was no pulpal necrosis in either group. O objetivo do presente estudo foi avaliar o aspecto histológico do complexo dentino-pulpar de cachorros quando capeado após a pulpotomia com etil-cianoacrilato e hidróxido de cálcio. Trinta dentes de cães foram divididos em 2 grupos de 15 da seguinte forma: Grupo 1 - Etil-cianoacrilato; Grupo 2 - Hidróxido de cálcio. A pesquisa foi realizada tomando-se todos os cuidados recomendados para o tratamento com os cães. Após 30 dias do procedimento realizado os espécimes foram submetidos ao preparo histológico e logo após foram avaliados de forma cega por um histologista. Os resultados foram analisados estatisticamente através do Teste Exato de Fisher. No grupo 1, 83,3% e no grupo 2, 100% dos dentes apresentaram a barreira de tecido duro (p = 0,478). A barreira de tecido duro contínua foi observada em 50% dos casos tratados com etil-cianoacrilato e em 75% dos com hidróxido de cálcio (p = 0,652). Pode-se concluir que tanto o grupo 1 como o grupo 2 induziram a formação da barreira de tecido duro, porém o grupo 2 teve um percentual maior do que o grupo 1, não havendo diferença estatisticamente significante; a diferença observada entre as estruturas das barreiras (contínuas e não-contínuas) não foi significante. A necrose pulpar não foi observada em nenhum grupo.